Hypoxia-induced inflammatory cytokine secretion in human adipose tissue stromovascular cells - O’Rourke, R. W.; White, A. E.; Metcalf, M. D.; Olivas, A. S.; Mitra, P.; Larison, W. G.; Cheang, E. C.; Varlamov, O.; Corless, C. L.; Roberts, C. T.; Marks, D. L. (Diabetologia, 2011)
Aims Hypoxia has been implicated as a cause of adipose tissue inflammation in obesity, although the inflammatory response of human adipose tissue to hypoxia is not well understood. The goal of this study was to define in vitro inflammatory responses of human adipose tissue to hypoxia and identify molecular mechanisms of hypoxia-induced inflammation. Methods The inflammatory milieu and responses of visceral (VAT) and subcutaneous (SAT) adipose tissue explants and purified stromovascular cells (SVFs) from obese and lean humans were studied in an in vitro hypoxic culture system using quantitative real-time PCR, ELISA, western blotting, immunofluorescence microscopy, flow cytometry and immunohistochemistry. Results Human adipose tissue in obesity demonstrates an increased leucocyte infiltrate that is greater in VAT than SAT and involves macrophages, T cells and natural killer (NK) cells. Hypoxic culture regulates inflammatory cytokine secretion and transcription of metabolic stress response genes in human adipose tissue SVF. Adipocyte diameter is increased and adipose tissue capillary density is decreased in obese participants. Inhibition of c-Jun terminal kinase (JNK) or p38 significantly attenuates hypoxia-induced SVF inflammatory responses. Hypoxia induces phosphorylation of p38 in adipose tissue. Conclusions Human adipose tissue in obesity is characterised by a depot-specific inflammatory cell infiltrate that involves not only macrophages, but also T cells and NK cells. Hypoxia induces inflammatory cytokine secretion by human adipose tissue SVF, the primary source of which is adipose tissue macrophages. These data implicate p38 in the regulation of hypoxia-induced inflammation and suggest that alterations in adipocyte diameter and adipose tissue capillary density may be potential underlying causes of adipose tissue hypoxia.